Investigating stress shielding spanned by biomimetic polymer-composite vs. metallic hip stem: A computational study using mechano-biochemical model - Tavakkoli Avval, Pouria; Samiezadeh, Saeid; Klika, Václav; Bougherara, Habiba (Journal of the mechanical behavior of biomedical materials, 2015)
Periprosthetic bone loss in response to total hip arthroplasty is a serious complication compromising patient's life quality as it may cause the premature failure of the implant. Stress shielding as a result of an uneven load sharing between the hip implant and the bone is a key factor leading to bone density decrease. A number of composite hip implants have been designed so far to improve load sharing characteristics. However, they have rarely been investigated from the bone remodeling point of view to predict a long-term response. This is the first study that employed a mechano-biochemical model, which considers the coupling effect between mechanical loading and bone biochemistry, to investigate bone remodeling after composite hip implantation. In this study, periprosthetic bone remodeling in the presence of Carbon fiber polyamide 12 (CF/PA12), CoCrMo and Ti alloy implants was predicted and compared. Our findings revealed that the most significant periprosthetic bone loss in response to metallic implants occurs in Gruen zone 7 (-43% with CoCrMo; -35% with Ti) and 6 (-40% with CoCrMo; -29% with Ti), while zone 4 has the lowest bone density decrease with all three implants (-9%). Also, the results showed that in terms of bone remodeling, the composite hip implant is more advantageous over the metallic ones as it provides a more uniform density change across the bone and induces less stress shielding which consequently results in a lower post-operative bone loss (-9% with CF/PA12 implant compared to -27% and -21% with CoCrMo and Ti alloy implants, respectively).
Keywords: Nylons; Postoperative Period; kyčelní kloub; kyčelní protézy; analýza metodou konečných prvků; mechanický stres; uhlík; Biomechanical Phenomena; slitiny; Hip Joint; biomimetické materiály; nylony; Models, Biological; Stress, Mechanical; pooperační období; Bone Remodeling; Alloys; biomechanika; Hip Prosthesis; biologické modely; Finite Element Analysis; kostní denzita; Carbon; remodelace kosti; Biomimetic Materials; Bone Density; modul pružnosti; Elastic Modulus